Modulus constraints in adaptive radar waveform design - Patton, L.K.; Rigling, B.D. (2008 IEEE Radar Conference, 2008)
Within the taxonomy of adaptive waveform generation methodologies is the family of arbitrary waveform design algorithms, which are capable of designing both the modulus and phase of a complex-valued waveform in response to changes in the operational environment of the sensor. Algorithms of this kind have been the subject of renewed research interest as a consequence of the relatively recent advances in linear RF power amplifiers, arbitrary waveform generators, and computational capability. In this paper, we use hardware considerations to argue that constraints on the maximum waveform modulus will generally supersede the total energy constraint commonly found in the literature. In order to illustrate the deleterious effects on system performance that can arise when these modulus constraints are not accounted for, we subjected recently published waveform design algorithms to maximum modulus limitations in simulation, and we present the results here. We also propose a novel arbitrary waveform design algorithm that accounts for both maximum modulus constraints and constraints on the waveformpsilas autocorrelation function. Simulation results that demonstrate the efficacy of this algorithm are presented.